RFID Enabled Chipless Humidity Sensor - Javed, N.; Habib, A.; Noor, T.; Amin, Y.; Tenhunen, H. (The Nucleus, 2019)
This paper presents a conformable 9-bit chipless radio frequency identification (RFID) humidity sensor, with an overall diameter of 12.4 mm. The semi-circle shaped tag is operating within a frequency band of 6-16 GHz. The tag structure is based on Taconic TLX-0 (substrate), copper (radiator) and a thin Kaptonïƒ’HN sheet (superstrate). The Kaptonïƒ’HN sheet is deployed over the innermost slot to obtain the sensing response from the respective resonant slot. A comparative analysis is derived by analyzing the tag design for Rogers RT/5880, Taconic TLX-0 and FR4 substrates, to observe the quality of resonant dips. Linearly polarized plane waves are used for excitation of the tag. A simple tag composition enables easy printability feature without requiring highly precise printing devices. This proposed tag can be utilized in many areas including pharmaceutical industries, beverage items, agriculture and in various low-cost RFID sensing applications.